Mediation role of cardiorespiratory fitness on association of physical activity and physical literacy among 8–12 years old children: the PAK-IPPL cross-sectional study - Hadier, Syed Ghufran; Yinghai, Liu; Long, Liu; Hamdani, Syed Danish; Hamdani, Syed Muhammad Zeeshan Haider (Frontiers in Pediatrics, 2024)
The effect of cardiorespiratory fitness (CRF) on the relationship of physical activity (PA), and physical literacy (PL) in 8-12 Pakistani children are largely unknown. Therefore, this study aims to examine the mediating role of CRF in the relationship between PA and PL in this demographicthe mediation role of cardiorespiratory fitness (CRF) on the relationship between PA and PL in 8-12 old school children.Methods: This cross-sectional study involved 1360 children aged 8-12 (mean age = 10.00, SD = 1.41 years) from 85 higher secondary schools in South Punjab, Pakistan. Data were collected during the 2020-2021 academic year using the Canadian Assessment of Physical Literacy-2 (CAPL-2) protocol to assess physical activity (PA), Body Mass Index (BMI), and PL levelsThis cross-sectional study was conducted among 1360 children aged 8-12 (mean age = 10.00, SD = 1.41 years) from 85 higher secondary schools in south Punjab Pakistan. Data was collected using the CAPL-2 protocol to evaluate MVPA, BMI, and PL level. CRF was measured using the PACER (Progressive Aerobic Cardiovascular Endurance Run) test. Descriptive statistics, independent samples t-tests, Chi-squared tests, and Generalized Additive Models for Location, Scale, and Shape (GAMLSS) were used for age and sex-specific CAPL-2 scoringThe study involved descriptive statistics, Independent Samples t-tests, Chi-squared tests, and GAMLSS for age and sex-specific CAPL-2 scoring for PL and CRF. Associations among components were evaluated through Pearson's correlation, multivariate logistic regression, and mediation analyses.Results: The study revealed that boys had significantly higher scores in CRF, PA, and PL across all age groups compared to girls (p < 0.001), with boys' scores being 20%, 10%, and 14% higher, respectively, than those of girls. Conversely, overweight children showed significantly reduced PA and PL levels (p < 0.001). An inverse correlation was found between BMI and CRF (r² linear = 0.022; quadratic = 0.028). CRF scores had significant negative correlations BMI (r = -0.143) and positive associations with MVPA, PA, DB, and PL (r ranging from 0.241 to 0.624). CRF was observed to partially mediate the association between MVPA and PL. The direct impact of MVPA on PL was significant and meaningful (β = 0.0022.4378, p <.001), )